PEMBERDAYAAN GURU TK MELALUI PELATIHAN SENI KRIYA UNTUK MENINGKATKAN KETERAMPILAN SENI ANAK USIA DINI - Yuniarti, Yuniarti (Kreasi: Jurnal Pengabdian Masyarakat, 2024)
The craft art training for kindergarten teachers in the PAUD Pelangi Cluster, Southeast Pontianak, aimed to enhance teachers’ understanding and skills in integrating craft art into early childhood learning, in line with the Merdeka Curriculum which emphasizes creative and innovative learning. The main issue addressed was the lack of teacher knowledge and skills in teaching craft art, which hindered the optimal development of children's creativity and self-expression. The training was conducted through several phases: preparation, material delivery, hands-on practice, field mentoring, and evaluation. The first day focused on theoretical foundations of craft art; the second day emphasized practical activities using materials such as clay, natural elements, and recycled items, including simulation with teachers acting as learning facilitators. Teachers demonstrated high enthusiasm through active participation and the quality of their art products. Evaluation using observation and satisfaction questionnaires indicated significant improvement in participants' competencies. The training effectively enhanced both theoretical understanding and practical skills, empowering teachers to design engaging, creative, and relevant learning experiences. Support from schools and parents in providing materials also contributed positively to the successful implementation of craft art in classrooms. This activity highlights the importance of continuous training and collaboration among teachers, parents, and schools.